Fundamentals of Entrepreneurship (ENT300) : Heaven Sea Cafe / Muhammad Azamuddin Izan ...[et al.] - Izan, Muhammad Azamuddin; Donald, Delvina; Zamsuri, Irfan Nurhaziq; Putit, Siti Hajijah; Henry, Stephenie Jane (2015)
Our company name is Heaven Sea Cafe. This business consists of five members. Each partner contributes certain amount of capital as agreed in contract. The major business activity is selling food and drinks. These concepts are due to customer request (local people and tourists). In addition, our cafe located at sea and has nice view. Our business is open at 2.00 pm until 1.00 am (Tuesday-Sunday) and our cafe closed on Monday. There are no inactive partners and all are entitled to participate in the business management. We agreed that Muhammad Azamuddin Bin Izan as our General Manager, Siti Hajijah Binti Putit as our Marketing Manager, Delvina Donald as our Operation Manager, Irfan Nurhaziq Bin Zamsuri as our Administration Manager and Stephenie Jane Henry as our Financial Manager. The General Manager is head of the company and responsible in plan, organize, direct and control the various aspect of business. Next, make sure all departments achieve their goals and solve the problem which is come in business and to make a decision. The Marketing Manager is responsible in find the strategic methods in promoting the business also ensure the customers' demands and tasks are fulfilled. The Operation Manager is responsible in managing operation. In addition, responsible in ensuring the company’s operation is at optimum and smoothly and giving out the duty for every staff. The Administration Manager is responsible in administration work and handles staff salary payment. The Financial Manager is responsible in handle company account, budgeting and cost control also prepare financial report.